THE DYNAMICS OF THE EXCHANGE RATE: IMPACT OF STOCK PRICE MOVEMENTS OF UNDERPRICING ISSUERS - Yandes, Jufri; Dwiyani Hadiwidjaja, Rini; Pujiwati, Ami; Fadillah, Syarif (UPT Publikasi Ilmiah UNISBA, 2024)
This study analyzes the impact of exchange rates on the fluctuation of issuer share prices during underpricing in initial public offerings from 2022 to 2023. The primary focus is on situations where the initial public offering share price is traded lower than the closing price on the first trading day, known as underpricing. The study aims to provide new insights into how exchange rate dynamics influence underpricing levels and contribute to both practice and science. Based on data from 83 companies that went public during this period, the research methodology includes statistical description, classical assumption tests, and linear regression analysis. The results indicate a significant relationship between exchange rates and underpricing. These findings offer a deeper knowledge of the factors influencing underpricing, particularly in the context of exchange rate fluctuations. The practical implications include aiding investors, issuers, and regulators in making informed decisions. Keywords : Exchange Rate, Initial Public Offering, Underpricing